2019
DOI: 10.1111/eci.13067
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy use in diabetic foot syndrome—from mechanisms of action to clinical practice

Abstract: Background Diabetes and its complications constitute a rising medical challenge. Special attention should be given to diabetic foot syndrome (DFS) due to its high rate of associated amputation and mortality. Negative pressure wound therapy (NPWT) is a frequently used supportive modality in a diabetic foot with ulcerations (DFUs). Design Here, we reviewed the current knowledge concerning the tissue and molecular mechanisms of NPWT action with an emphasis on diabetes research followed by a summary of clinical DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 59 publications
0
43
0
1
Order By: Relevance
“…190 Some evidence demonstrates that NPWT results in more pro-angiogenic and antiinflammatory molecular conditions in wounds. 191 NPWT with instillation (NPWTi) is a system incorporating both instillation (using one of various types of sterile fluids) and aspiration that is intended to cleanse, and possibly disinfect, wounds. 192 While many published studies have demonstrated the safety and wound healing efficacy of NPWT/NPWTi, the quality of most is relatively low, few have addressed diabetic foot complications, 193 and none have specifically addressed if there was benefit in resolving evidence of wound infection.…”
Section: Recommendation 27mentioning
confidence: 99%
See 1 more Smart Citation
“…190 Some evidence demonstrates that NPWT results in more pro-angiogenic and antiinflammatory molecular conditions in wounds. 191 NPWT with instillation (NPWTi) is a system incorporating both instillation (using one of various types of sterile fluids) and aspiration that is intended to cleanse, and possibly disinfect, wounds. 192 While many published studies have demonstrated the safety and wound healing efficacy of NPWT/NPWTi, the quality of most is relatively low, few have addressed diabetic foot complications, 193 and none have specifically addressed if there was benefit in resolving evidence of wound infection.…”
Section: Recommendation 27mentioning
confidence: 99%
“…NPWT involves the application of a special wound dressing attached to a vacuum suction machine that aspirates wound and tissue fluid from the treated area into a canister . Some evidence demonstrates that NPWT results in more pro‐angiogenic and anti‐inflammatory molecular conditions in wounds . NPWT with instillation (NPWTi) is a system incorporating both instillation (using one of various types of sterile fluids) and aspiration that is intended to cleanse, and possibly disinfect, wounds .…”
Section: Treatmentmentioning
confidence: 99%
“…Whether it constitutes a novel mechanism of NPWT action requires further research. NPWT's local mechanism of action at the tissue level has been well documented in a recent review [26]. NPWT results in the promotion of wound contraction, tissue granulation, vessel proliferation, neoangiogenesis, epithelialization, and removal of excess extracellular fluid [26].…”
Section: Discussionmentioning
confidence: 99%
“…They were assigned either to the standard therapy (ST) group or to the combined standard therapy with NPWT group, with each treatment time lasting 8 ± 1 days. Patients were nonrandomly assigned to the NPWT group but rather chosen based on local and international research and clinical practices, as well as the guidelines concerning NPWT use in DFU, most of which take wound area into account [26, 27]. In short, patients with ulcerations ≤ 1.0 cm 2 were allocated to the ST group, and the remaining patients were assigned to the NPWT group.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is a devastating disease with more than 400 million people affected globally 1. Chronic ulcers with deep tissue damage in patients with diabetes leads to a high rate of amputation and mortality.…”
Section: Introductionmentioning
confidence: 99%